Analisis Kemampuan Gerak Motorik Anak dalam Permainan Tradisional Bola Kasti di Kelas V Sekolah Dasar Negeri 105283 Klambir V Kampung - Dewi Anggraini; Layil Safitri; Syarifah Ainun Harahap (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
Motor skill development constitutes a fundamental aspect of children's physical growth and plays a crucial role in supporting their participation in various physical activities. This study aimed to analyze the motor skill abilities of fifth-grade students through their participation in the traditional game of kasti at State Elementary School 105283 Klambir Lima Kampung during the 2024/2025 academic year. A qualitative research design employing a case study approach was utilized to explore students’ motor performance in a natural learning context. Data were collected through direct observations of students’ movements during gameplay and interviews with teachers and students to obtain complementary information regarding motor development. The findings revealed variations in students’ motor abilities, particularly in running, throwing, catching, and hitting the ball. Several students demonstrated well-developed coordination, balance, agility, and movement control, whereas others encountered difficulties in hand–eye coordination and maintaining balance during dynamic activities. Age, previous physical activity experiences, and environmental stimulation emerged as influential factors affecting students’ motor performance. The study concludes that the traditional game of kasti serves as an effective, engaging, and contextually relevant medium for fostering children’s gross motor development and can be integrated into elementary physical education practices to enhance students’ motor competencies.